Study on the bonding mechanism of multilayer copper with nickel sheet in ultrasonic welding process - Fuxing Ye; Yonghui Wang; Hewan Lu; Yongming Guo (Materials Research Express, 2022)
The metal-plastic flow and bonding strength of three-layer copper (Cu) with single-layer nickel (Ni) joints via ultrasonic welding were investigated in this study. With the increase of welding time from 0.3 to 0.5 s, the weld bonding density between different layers’ interface increased gradually and approached about 95 ± 1.5%. Electron backscatter diffraction (EBSD) analysis of different regions of the welded joint revealed that the metal grains in the 1st layer became relatively small and elongated, while the 2nd and 3rd layers tended to be equiaxed grains. The joint bonding strength of T-peel tests changed with welding time and had two kinds of fracture models (nugget pullout and interfacial fracture). Compared with the bonding strength of the 1st-2nd and 3rd-4th interface, the 2nd-3rd interface of joints had the highest bonding strength of 400.6 N with nugget pullout fracture model at welding time of 0.4 s. In addition, the much higher hardness of the 1st layer is attributed to the strong plastic deformation of the 1st layer, while the dynamic recovery and dynamic recrystallization of the metal of the 2nd layer resulted in the decrease of hardness.